Konsep Pemikiran Tasawuf Falsafi (Ittihad, Hulul Dan Wihdatul Wujud) - Devi Umi Solehah (Medan Resource Center, 2021)
Falsafi Sufism is a concept of Sufism teaching that knows God (ma'rifat) with a ratio of philosophical approaches to a higher level, not only knowing God (ma'rifatullah) but higher than that is wihdatul embodiment (the unitary form of creatures). It can also be said that Falsafi Sufism is a Sufism that is rich in philosophical thought. Philosophical Sufism is an interesting topic to discuss. In this paper, we will discuss the formation and development of philosophical thought (Falsafi Sufism) which consists of: the understanding of philosophical Sufism, the background of philosophical Sufism, the historical development of philosophical Sufism, the figures of philosophical Sufism, the characteristics of philosophical Sufism, and the main teachings of philosophical Sufism.